Mediterranean red coral as a spawning ground for cuttlefish - Federica Maggioni; Lorenzo Bramanti (Global Journal of Ecology - Peertechz Publications, 2022)
The Mediterranean red coral (Corallium rubrum) is a long-lived and slow-growing gorgonian, which suffered intense exploitation due to its precious calcium carbonate skeleton used in jewelry and traded worldwide [1].